2023
DOI: 10.3389/fpsyt.2023.1056210
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of interventions for treatment-resistant depression: A systematic review

Abstract: BackgroundThe extraordinarily high prevalence of treatment-resistant depression (TRD), coupled with its high economic burden to both healthcare systems and society, underscore how critical it is that resources are managed optimally to address the significant challenge it presents.ObjectiveTo review the literature on economic evaluation in TRD systematically, with the aim of informing future studies by identifying key challenges specific to the area, and highlighting good practices.MethodsA systematic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 98 publications
(129 reference statements)
0
0
0
Order By: Relevance
“…However, results have shown that functional targets can be influenced by the processing of resting-state MRI data, leading to variability in target identification and raising questions about the stability of such methods. Furthermore, the effectiveness of interventions based on functional targets remains to be fully explored 39,40 . On the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…However, results have shown that functional targets can be influenced by the processing of resting-state MRI data, leading to variability in target identification and raising questions about the stability of such methods. Furthermore, the effectiveness of interventions based on functional targets remains to be fully explored 39,40 . On the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…Offering therapies tailored to the pathophysiology of each patient is also essential to avoid the additional costs associated with therapeutic error in TRD. The economic evidence for interventions in TRD is poorly developed (Hannah et al , 2023). The established acute and maintenance efficacy in TRD, the beneficial effects on suicidality, the rapid onset of symptomatic improvement, and the superiority over second generation antipsychotics (i.e.…”
mentioning
confidence: 99%